Mechanical Thrombectomy in Stroke in Nonagenarians: Useful or Futile? - Mendes Pinto, M (2020)
Background: Mechanical thrombectomy is the standard treatment in acute ischemic stroke due to large vessel occlusion, but there is limited evidence about its efficacy in very old patients. We sought to analyse safety and effectiveness of mechanical thrombectomy in nonagenarian versus octagenarian patients. Methods: We included consecutive patients with acute ischemic stroke due to large vessel occlusion subjected to mechanical thrombectomy, during 29 months in a tertiary center. Patients were divided into two sub-groups, according to age: 80-89 and >90 years old. Recanalization, complications, functional outcome and mortality at discharge and at 3 months were compared. Multivariable analysis was performed to identify independent predictors of functional outcome at 3 months of follow-up, assessed by the modified Rankin Scale. Results: A total of 128 octogenarians (88.9%) and 16 nonagenarians (11.1%) met the inclusion criteria. Successful revascularization was achieved in 87.5% of octagenarians and in 81.3% of nonagenarians (p = 0.486). Symptomatic hemorrhage occurred in 3.1% and 6.3% of younger and older patients, respectively (p = 0.520). Cerebral edema occured in 35.2% of octagenarians versus 25.0% of nonagenarians (p = 0.419). Functional independence (mRS ≤ 2) at 3 months was achieved in 28 (22.6%) and 5 (31.3%) of octagenarians and nonagenarians, respectively (p = 0.445). Mortality at 3 months was not significantly higher in nonagenarians (37.5%) versus octagenarians (33.9%, p = 0.773). Conclusions: No significant diferences were found in functional outcome, mortality, recanalization and complication rates between octagenarians and nonagenarians submitted to mechanical thrombectomy, underlining that patients should not be excluded from mechanical thrombectomy based on age alone.